Exploring the Role of Green Marketing in Consumer Purchasing Behavior toward Electric Vehicles in Vietnam - Nguyen, Minh Bach; Kottika, Efthymia, 1982-; Vinš, Marek; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The thesis aims to determine the Vietnamese people's stands and viewpoints on electric vehicles, particularly customers’ evaluations of electric vehicle manufacturers’ green marketing. Based on this, the research identifies the key motivations and barriers that influence their awareness and willingness to purchase electric vehicles. The research is conducted using a qualitative approach through in-depth interviews with Vietnamese customers and they are invited to share their perceptions on the topic. The research results show that Vietnamese consumers' awareness is increasingly enhanced through the information they access from green marketing campaigns on social networks. Consequently, people will tend to purchase electric vehicles if the safety of these vehicles is improved, charging station infrastructure is developed, and battery quality is enhanced. Besides, green marketing campaigns should be specifically developed according to each group of consumers and bring real benefits. Lastly, companies should enhance their reputation by maintaining transparency in production processes and obtaining third-party certifications.
Vedoucí práce: Efthymia Kottika
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses